Development of Ruhiology-based Islamic Counselling Guidance Module for Student Stress Management during Online Learning - Ushuluddin, Achmad; Affan, Mohammad (RSF Conference Series: Business, Management and Social Sciences, 2023)
Stress levels increased throughout the online learning period due to the COVID-19 pandemic. High learning demand, copious tasks assigned by teachers, high targets set for student achievements, and even hurdles in using digital technology were some factors triggering stress among students. Under such conditions, the development of Islamic counselling guidance services is required to assist students in managing stress so that it does not lead to negative consequences, such as reduced motivation to study or even depression. Accordingly, the current research aims to produce a module that guidance and counselling teachers and counsellors can use to provide counselling services in the form of stress management for students, particularly when they engage in online learning. The perspective used as the basis for developing this module is ruhiology, a perspective in Islamic psychology. Stress management in the ruhiology perspective is based on ruhani awareness as the main subject within the human self, which can control, manage, regulate, and even prevent stress. The method used is research and development (R&D) using the ADDIE model covering five stages: analyze, design, development, implementation, and evaluation. After testing or feasibility study was done by experts and usability testing was done by guidance and counselling teachers, findings show that the module for developing ruhiology-based Islamic counselling guidance is deemed highly viable to follow up and implement in the broader field test stage in order to help students manage their stress during online learning.